Computer Simulating Harvesting Forces Using 3D Modeling for the Olive Tree - Glavan, Dan Ovidiu; Glavan, Andreea Ioana; Babanatsas, Theoharis; Merce, Roxana Mihaela Babanatis (Advanced Aspects of Engineering Research Vol. 1, 2021)
The paper presents the results of the study regarding the influence of shaking forces on olive tree harvesting systems. Shaking forces can be released through several methods. In order to use an automatic system for harvesting, we must calculate the necessary force of vibration to shake the olive tree. Important is the end result, namely the shaking force and the cadence of shaking speed. Mechanical and automatic harvesting methods collect more olives than traditional methods but may damage the olive trees. In order to prevent this damage, we need to calculate the necessary shaking force. An original research method is proposed to simulate shaking forces using a 3D olive tree model with Autodesk Inventor software. In the experiments, we use different shaking forces and various shaking speeds. We also use different diameters of the olive tree trunk. We analyze the results from this experiment to determine the optimal shaking force for harvesting olives without damaging the olive tree. All results were satisfactory on highest forces without breaking the olive tree.